Australian midwives' practice domain. - Cullen, Miriam C. (Curtin University, 1997)
This exploratory, descriptive research used a case study approach to analyse the role of the midwife in providing maternal and infant care in Australia. Midwives from the states of New South Wales, Victoria and Western Australia comprised the target population. These midwives were considered to be representative of the general midwifery population practising in the diverse settings of Australia.A triangulation of methods (Denzin, 1970) was used for data collection. This included observational field work, a questionnaire survey of a randomly selected sample of registered midwives (n=1754), and in-depth interviews (n=75), using a grounded theory approach (Glaser and Strauss, 1967; Strauss and Corbin, 1990).The questionnaire, in-depth interviews and observational field work addressed the practice of midwives:1. as documented in policies and procedures in practice settings.2. as defined by the Australian College of Midwives Incorporated in Standards for the Practice of Midwifery (1989), based on the International Confederation of Midwives' Definition of a Midwife (World Health Organisation, 1976).Data obtained through the survey questionnaire were analysed using descriptive analysis (Wilson, 1985) to portray a summarization of the entire data set. A thematic content analysis was used for the open-ended questions of the survey (Burnard, 1991). In an attempt to discover the 'how and why' questions associated with the study's survey findings, the constant comparative method of analysis of data from in-depth interviews was deemed appropriate (Glaser, 1978; Field and Morse, 1985; Chenitz and Swanson, 1986). This allowed a more abstract level of conceptualization that led to the development of a paradigm reflective of the midwives' practice domain (Strauss and Corbin, 1990).Lack of opportunities to practise throughout all stages of pregnancy and childbirth was identified as the major problem limiting the Australian midwives' practice domain. An explanatory process of Optimising Opportunities for Holistic Midwifery Practice emerged explaining midwives' actions and interactions throughout the four stages of optimising: revealing the image; influencing decision making; changing the paradigm; and expanding the profession.The findings of the study provide an analysis of Australian midwifery practice that considers factors facilitating and/or impeding the professional role and development of Australian midwives, and their ability to provide care that meets consumer needs.